Laws of thermodynamics and human health - G. L. Apanasenko (Сеченовский вестник)
The article discusses the fundamental concept of life and health as a manifestation of solar energy transformation into other types of energies (thermal, mechanical, electric, etc.) providing life. The article states that the efficiency of intracellular energy as a manifestation of mitochondrial function (the final stage of solar energy transformation) indicates the organism’s resistance to external and internal negative influences. This provides the opportunity of quantitative health (and viability) estimation of an individual. Neither endogenous risk factors nor diseases are found above a certain level of energy production. This is a quantitative (“safe”) health level. The article demonstrates that if the majority of population goes beyond “safe” health level results in CNID epidemic. The article postulates the necessity supplement the “industry of illness” (establishment of Health Мinistries) with the “industry of health”, responsible for maintenance and increase of the biosystem energy potential.